Natural rubber nanocomposites based on hybrid filler of zinc nanoparticles and carbon nanotubes: Electrical conductivity and other related properties - N. Thongkong; S. Wisunthorn; S. Pichaiyut; C. Nakason; S. Kiatkamjornwong (eXPRESS Polymer Letters)
Hybrid filler of carbon nanotubes (CNT) and zinc oxide (ZnO) nanoparticles were prepared and then mixed with natural rubber (NR). The ZnO nanoparticles were first synthesized by the sol–gel method. The NR-CNT/ZnO nanocomposites were prepared by latex mixing. Various proportions of ZnO in the CNT/ZnO hybrid filler were tested by mixing with NR to eventually form NR-CNT/ZnO nanocomposites. It was found that the optimum ZnO content in CNT/ZnO hybrid filler was about 3 phr. These ZnO contents provided the NR hybrid composite with superior mechanical properties in terms of tensile strength and modulus, together with good electrical conductivity and dielectric properties. In addition, stress relaxation tests revealed stronger filler network formation after incorporation of CNT-ZnO hybrid filler into the NR matrix. It might be due to electrostatic interactions between CNT and ZnO, also contributing to high electrical conductivity and dielectric properties of the NR-CNT/ZnO composites, when compared to a solely CNT filled NR composite. Furthermore, the Payne effect and morphological properties were qualitatively analyzed, indicating that CNT dispersion was finer in the NR-CNT/ZnO composites having about 1 to 3 phr ZnO content in CNT/ZnO. Higher contents of ZnO in CNT/ZnO hybrid filler caused large filler aggregates degrading mechanical and electrical properties.